Analyse des facteurs socioculturels et survenue des troubles musculosquelettiques : le cas des couturières en Tunisie - Raouf Ghram; Catherine Fournier; Taoufik Khalfallah; Francis Six (Perspectives Interdisciplinaires sur le Travail et la Santé)
The current context of globalization sometimes involves work relocation and internationalization, which sometimes lead to work situations unfavourable for the preservation of workers’ health. Indeed, technology transfers require an understanding of the contextual determining factors that can influence work situations. Here, we find in particular the sociocultural specificities that we addressed in this study. Their consideration provided us with a better understanding of operator work situations in the clothing industry in Tunisia. In fact, we note the interest in taking these aspects into consideration in order to plan appropriate work situations that respect health.